Antler characteristics are highly heritable but influenced by maternal factors. Issue 8 (10th August 2016) - Michel, Eric S.; Demarais, Stephen; Strickland, Bronson K.; Smith, Trent; Dacus, Chad M.
ABSTRACT: The extent of heritability and predictability of phenotypic characteristics influences directional selection of a species' phenotype by the environment or through anthropogenic selection. Heritability is often related to evolvability, whereas predictability describes the efficiency of using one characteristic to predict another. Characteristics that are highly heritable and predictable may be easily selected for or against. Discrepancy exists in previous reports of heritability estimates for antler characteristics of white‐tailed deer ( Odocoileus virginianus ) and if antler size of young males can be used to predict antler size later in life. We assessed the level of heritability of 6 antler characteristics using captive white‐tailed deer aged 2.5–5.5 years and tested if antler size of 1.5‐year‐old males was a reliable predictor of antler size at 3.5 years after accounting for the effects of litter size and parturition date. Antler characteristics were moderately to highly heritable, whereas 1.5‐year‐old antler size alone was only a moderate predictor of antler size at 3.5 years. However, predictability nearly doubled after accounting for parturition date and litter size. White‐tailed deer antler characteristics are moderately to highly heritable and although hunter selection may influence long‐term phenotype for some ungulates, hunter selection is unlikely to manipulate white‐tailed deer population‐level phenotype because predicting future antler size is inefficient and individual reproductive success is variable. © 2016 The Wildlife Society.